2013
DOI: 10.1159/000353760
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Metformin Use in Obese Nondiabetic Children and Adolescents

Abstract: Objective: Childhood obesity has become epidemic and has been accompanied by an increase in prevalence of type 2 diabetes (T2DM) in youth. Addressing obesity and insulin resistance by drug treatment represents a rational strategy for the prevention of T2DM. A systematic review was performed to evaluate the effectiveness of metformin in reducing weight and ameliorating insulin resistance in obese nondiabetic children. Methods: A PubMed database search was conducted, using ‘metformin', ‘obesity', ‘insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 33 publications
2
41
0
2
Order By: Relevance
“…The present review focuses on psychological treatments for childhood and adolescent overweight and obesity. Please refer to the following reviews for more information on bariatric surgery for adolescents (Barnett, 2013) and pharmacological treatments for children and adolescents (Brufani et al, 2013).…”
Section: Methods Search Strategymentioning
confidence: 99%
“…The present review focuses on psychological treatments for childhood and adolescent overweight and obesity. Please refer to the following reviews for more information on bariatric surgery for adolescents (Barnett, 2013) and pharmacological treatments for children and adolescents (Brufani et al, 2013).…”
Section: Methods Search Strategymentioning
confidence: 99%
“…In any case, metformin may be a useful adjuvant treatment in obese and/or insulin-resistant children and adolescents, although its role in this setting is still unclear [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Some authors concluded that a limited period of such a treatment may help weight control and might be used to encourage those children who have been refractory to weight loss for continuing the non-pharmacological programs. These results should be confirmed in studies with a longer follow-up period [21, 22]. The combination of diet and exercise followed by metformin in the early phase of “IR” may reduce or delay both atherosclerosis and its complications associated with diabetes.…”
Section: Metformin and Other Drugs For The Ir Therapy In Other Diseasmentioning
confidence: 90%